'Life Is Tight Here': Displacement and Desire amongst Syrian Refugee Women in Jordan. Issue 1 (1st June 2021) - Chalmiers, Morgen A.
Abstract: Since the civil war began in 2011, 5.5 million Syrians have fled their home country and are now living as refugees. Building upon anthropological studies of precarity, the article draws upon 14 months of person-centered ethnographic fieldwork to examine the contextual specificities of Syrian women's protracted displacement in Jordan. By foregrounding bodily experience as described by three interlocutors during person-centered interviews, the article considers how subjectivities are reshaped under such conditions. The narratives analysed here illustrate how the precarity of displacement fosters an embodied sense of tightness, constriction and stagnation while reconfiguring temporal horizons and rendering visions of imagined futures increasingly myopic.